"A New and Coherent Strategy?" Presidential attention and rhetoric in the era of Indian self-determination. (November 2021) - Flaherty, Anne F. Boxberger
Abstract: This paper explores the dynamics of presidential attention and rhetoric on Native issues and peoples during the self-determination era. Using data from all public statements and papers of the presidents from 1969 to 2016, the work analyzes the level of attention and rhetorical frames of each president from Nixon to Obama, with additional comments on Trump. The analysis reveals that most presidents have given relatively little attention to Native issues compared to their overall volume of public statements, with Democratic Presidents Clinton and Obama offering the most attention. In addition, presidents have used very different rhetorical frames to address Native issues and peoples in their public statements. Presidential rhetoric has been characterized by fluctuating attention and frames, and presidents have not consistently supported Nixon's "new and coherent strategy" throughout the self-determination era.